2022
DOI: 10.2196/35847
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Personalized Recommendations to Support Caregivers of People Living With Dementia: Mixed Methods Study

Abstract: Background Estimates suggest that 6.2 million Americans aged ≥65 years are living with Alzheimer dementia in 2021, and by 2060, this number could more than double to 13.8 million. As a result, public health officials anticipate a greater need for caregivers of persons with Alzheimer disease or related dementia and support resources for both people living with dementia and their caregivers. Despite the growing need for dementia caregiver support services, there is a lack of consensus regarding how t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Consistent with previous research on digital interventions among caregivers, web-based delivery of the program also appeared to be well-liked and allowed caregivers to complete activities at their convenience [ 33 , 34 ]. Multicomponent, self-administered, web-based interventions have previously been shown to improve depression and anxiety among AD/ADRD caregivers and may have broader applications in the future [ 35 ].…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with previous research on digital interventions among caregivers, web-based delivery of the program also appeared to be well-liked and allowed caregivers to complete activities at their convenience [ 33 , 34 ]. Multicomponent, self-administered, web-based interventions have previously been shown to improve depression and anxiety among AD/ADRD caregivers and may have broader applications in the future [ 35 ].…”
Section: Discussionsupporting
confidence: 74%
“…Eighty-five papers covering 49 studies were included (some studies were demonstrated in a series of papers). The included studies consisted of 19 RCTs [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], 10 non-RCTs [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ], 4 descriptive quantitative studies [ [57] , [58] , [59] , [60] ], 4 qualitative studies [ [61] , [62] , [63] , [64] ] and 12 mixed-methods studies [ [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ], see Appendix A . These studies were conducted in America ( n = 25), Netherlands ( n = 4), Canada ( n = 2), France ( n = 1), India ( n = 1), China ( n = 1), Australia ( n = 3), United Kingdom ( n = 2), Spain ( n = 1), Greece ( n = 1), Ireland ( n = 1), Korea ( n = 1), Iran ( n = 1) and multiple European countries ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…First, technical problems were identified in 9 studies, such as busy signals, visual problems caused by poor contact and unclear site navigation [ 31 , 36 , 43 , 47 , 63 , 69 , 71 , 72 , 75 ]. Second, poor computer literacy of family caregivers was also a barrier to program implementation [ 38 , 65 , 68 , 69 ]. Online programs are more flexible to use for young family caregivers with internet access.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family caregivers faced the dual concern of keeping their vulnerable loved ones and themselves safe from COVID-19, while also experiencing limited access to acute care, primary care, home care, and social care programs. They also had reduced opportunities for social activities and experienced higher levels of sleep disturbances, fatigue, anxiety, depression, and burnout [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%